2021
DOI: 10.1371/journal.pone.0244347
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of depressive symptoms in Syrian refugees and Turkish maintenance hemodialysis patients during COVID-19 pandemic

Abstract: Introduction Pneumonia of unknown cause was detected on 30 December 2019 in China. It was categorized as an outbreak and named as COVID-19 by the World Health Organization. The pandemic affects all people, but patient groups such as hemodialysis (HD) patients have been particularly affected. We do not know if refugees suffered more during the outbreak. In this study, we compared depressive symptom frequency between Syrian refugee HD patients and Turkish ones. Methods The study had a single-center, cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Literatürde yer alan diğer çalışmalar genel olarak salgınlar ve COVID-19 pandemisi döneminde pandemi dışındaki sağlık hizmetleri sunumunun azaldığını göstermektedir. [17][18][19][20]23,24,[27][28][29][30] Bununla birlikte, literatürde yer alan çalışmalarda, pandemi hastaları dâhil edildiğinde hizmet sunumundaki azalış değerlendirilememiştir. Birçok hastanede, diğer sağlık hizmetleri sunumundaki azalışın pandemi hastalarının yatışı ile telafi edilebileceğini düşünmek mümkündür.…”
Section: Discussionunclassified
“…Literatürde yer alan diğer çalışmalar genel olarak salgınlar ve COVID-19 pandemisi döneminde pandemi dışındaki sağlık hizmetleri sunumunun azaldığını göstermektedir. [17][18][19][20]23,24,[27][28][29][30] Bununla birlikte, literatürde yer alan çalışmalarda, pandemi hastaları dâhil edildiğinde hizmet sunumundaki azalış değerlendirilememiştir. Birçok hastanede, diğer sağlık hizmetleri sunumundaki azalışın pandemi hastalarının yatışı ile telafi edilebileceğini düşünmek mümkündür.…”
Section: Discussionunclassified
“…Almost 60% of these patients were male, and a vast majority (84%) had a poor socioeconomic background 23 . Another study that was done during the COVID-19 pandemic reported that 42.7% of Turkish and 72.7% of the Syrian population is suffering from depression 24 . Another study reported 68% depressive symptoms among dialysis patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two studies focused on major depressive disorder or depressive symptoms (Acarturk et al, 2018, 2021; Ahmad et al, 2021; Böge et al, 2020; Borho et al, 2020; Braun-Lewensohn et al, 2019; Cheung Chung et al, 2018; Chung & Shakra, 2022; Chung et al, 2017, 2021; Chung, AlQarni et al, 2018; Chung, Shakra et al, 2018; Demir et al, 2020; Euteneuer & Schäfer, 2018; Fuhr et al, 2019; Gammouh et al, 2015; Georgiadou et al, 2018, 2020; Javanbakht et al, 2019; Mahmood et al, 2019; Marwa, 2016; McGrath et al, 2020; Mohammad et al, 2018; M’zah et al, 2019; Naal et al, 2021; Naja et al, 2016; Oda et al, 2021; Okenwa-Emegwa et al, 2019; Poole et al, 2018; Rizkalla & Segal, 2018, 2019; Röhr et al, 2020; Schlechter et al, 2021; Sengoelge et al, 2019; Sevinc et al, 2021; Sim et al, 2018; Stevenson et al, 2019; Tekeli-Yesil et al, 2018; Tinghög et al, 2017; Uygun, 2021; Woltin et al, 2018; Yalim, 2021). The most used instrument was the Hopkins Symptom Checklist 25-items (HSCL-25), and the prevalence of positive screening results ranged from 34.7% to 59.4%.…”
Section: Prevalence Risk Factors and Assessment Methods For Psychiatr...mentioning
confidence: 99%
“…Most of the studies took place in non-camp settings, followed by studies in refugee camps or in both settings. Sixteen studies were comparative between refugee populations in different settings or refugees and local populations in the same setting (Alduraidi et al, 2020; Basheti et al, 2015; Böge et al, 2020; Cheung Chung et al, 2018; Chung et al, 2021; Chung, AlQarni et al, 2018; Demir et al, 2020; Khamis, 2022; Powell et al, 2020; Saab et al, 2020; Schlechter et al, 2021; Sevinc et al, 2021; Stevenson et al, 2019; Tekeli-Yesil et al, 2018; Woltin et al, 2018; Yalim, 2021).…”
Section: Origin Of the Studies And Demographicsmentioning
confidence: 99%